2011
DOI: 10.5248/115.163
|View full text |Cite
|
Sign up to set email alerts
|

Calocera bambusicola sp. nov. and C. sinensis newly recorded from Taiwan

Abstract: Calocera bambusicola is presented as a new species, based on specimens collected from rotten culms of bamboo (Pseudosasa usawai) near a sulfur hot spring on Yangminshan mountain in Yangminshan National Park, Taipei, Taiwan. This new species morphologically resembles C. sinensis but differs in its much smaller basidiocarps, narrower basidiospores, much narrower contextual hyphae, and growth on bamboo culms. ITS differences also separate these two species. A key to species of Calocera with nodose-septate hyphae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Although some genera based on these criteria are not monophyletic ( Shirouzu et al 2013a ), we retained those generic concepts because no phylogenetic-based classification system has yet been established for Dacrymycetes . In similar situations, new species have been described according to the traditional system based on morphological criteria ( Shirouzu et al 2009 , 2013b , Wu et al 2011 , Delivorias et al 2012 ).…”
Section: Methodsmentioning
confidence: 99%
“…Although some genera based on these criteria are not monophyletic ( Shirouzu et al 2013a ), we retained those generic concepts because no phylogenetic-based classification system has yet been established for Dacrymycetes . In similar situations, new species have been described according to the traditional system based on morphological criteria ( Shirouzu et al 2009 , 2013b , Wu et al 2011 , Delivorias et al 2012 ).…”
Section: Methodsmentioning
confidence: 99%
“…Reid) Sheng H. Wu, and P. yunnanensis C.L. Zhao had been discovered in China (Wu, 2003;Dai, 2011;Wu et al, 2019). During field investigations on macrofungi diversity in the tropical areas in Yunnan Province, China, several collections of Si et al 10.3389/fmicb.2023.1151365 Frontiers in Microbiology 02 frontiersin.org…”
Section: Introductionmentioning
confidence: 99%
“…Fr. is known for its distinctive characteristics, stipitate, fasciculate or scattered, gelatinous basidiomata, dendroid or staghorn-like, subclavate to clavate basidia and probasidia, as well as cylindrical to reniform, septate or non-septate basidiospores ( Fisher 1931 ; Lowy 1971 ; Peng et al 1992 ; Wu et al 2011 ; Shirouzu et al 2017 ). Recent phylogenetic analyses of the class Dacrymycetes demonstrated that Calocera was polyphyletic and species in the genus are scattered throughout the family Dacrymycetaceae together with most of the species of Dacrymyces Nees (1817 : 89) as well as a few species from other genera such as Dacryopinax G.W.…”
Section: Introductionmentioning
confidence: 99%